Understanding growth and poverty : theory, policy, and empirics - Nallari, Raj, 1955- (Directions in development (Washington, D.C.), 2011)
The literature on growth and poverty is voluminous and still evolving. This title distills the most important lessons from developing countries' experience with growth and poverty. It provides a broad understanding of the impact of economic policies on growth and poverty reduction in developing countries. After describing basic economic relationships that summarize the workings and the measurement of the macroeconomy--and after confirming that growth is the most critical factor in alleviating poverty--the book turns to individual policy areas. These include the various roles of government, amo.